Disease Control Priorities, Third Edition (Volume 9): Improving Health and Reducing Poverty 2017
DOI: 10.1596/978-1-4648-0527-1_ch17
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics: Risks, Impacts, and Mitigation

Abstract: for their valuable technical and editorial contributions to the chapter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
449
0
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 529 publications
(474 citation statements)
references
References 123 publications
2
449
0
23
Order By: Relevance
“…5 We found other integrative estimates of the magnitude of pandemic risk in two partially proprietary sources. 17,18 Several studies have examined specific dimensions of the economic impacts of annual influenza, such as direct costs, e.g. medical and hospitalizations costs, and indirect costs, e.g.…”
Section: Economic Losses From Influenzamentioning
confidence: 99%
See 2 more Smart Citations
“…5 We found other integrative estimates of the magnitude of pandemic risk in two partially proprietary sources. 17,18 Several studies have examined specific dimensions of the economic impacts of annual influenza, such as direct costs, e.g. medical and hospitalizations costs, and indirect costs, e.g.…”
Section: Economic Losses From Influenzamentioning
confidence: 99%
“…A modelling exercise for the insurance industry concluded that the annual risk of an influenza outbreak on the scale of the 1918 pandemic lies between 0.5% and 1.0%. 18 For more severe pandemics, we fitted a parametrized exceedance probability function to modelled data that had been previously reported. 18,35…”
Section: Exceedance Probability Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Editors of DCP3’s first eight volumes and authors of specific chapters in volume 9 (on rehabilitation, 38 on pathology, 39 on palliative care, 40 and pandemic preparedness 41 ) constructed the 21 essential packages listed in panel 3. The authors of this Review then consolidated those policies and formats into a common level of aggregation and a common structure (eg, screening was not considered an intervention by itself but only in conjunction with the indicated response).…”
Section: The Dcp3 Approachmentioning
confidence: 99%
“…Research on the 1918 influenza H1N1 pandemic and recent epidemics and pandemics has shown a range of estimated losses (panel). [1][2][3][4][5][6][7] A limitation in assessing the economic costs of outbreaks is that they only capture the impact on income. Fan and colleagues 8 recently addressed this limitation by estimating the "inclusive" cost of pandemics: the sum of the cost in lost income and a dollar valuation of the cost of early death.…”
Section: Financing Of International Collective Action For Epidemic Anmentioning
confidence: 99%